Al-Qur’an Memorization Animation: Solusi Mudah Menghafal Al-Qur’an Pada Anak TPA Nurul Huda - Uswatun Khasanah; Riska Wahyuni; Moh. Rusli; Mochmammad Abhipraya Aryaputra; R. Panji Hermoyo (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
TPA has a goal to improve students' ability to read, write, understand and practice the Qur'an. At TPA Nurul Huda, which is located in Bendo Hamlet, RT 03, RW 04, Karanganyar Village/Sub-district, Ngawi Regency has a problem, namely the low memorization ability of students. This is caused by several factors, including the heterogeneity of children's ages between 5 and 12 years, unattractive media and teachers who have difficulty finding ways to improve children's ability to memorize the Qur'an. The purpose of this community service PKM activity is to provide solutions to the problems experienced by TPA Nurul Huda. The solution given is an animated video learning media called Al-Qur’an Memorization Animation. Service activities are carried out for 4 months starting from June to September 2021. The methods used in this service are socialization, training (implementation), mentoring, measurement, and regeneration. The result of this activity is that the children of TPA Nurul Huda experienced a significant increase in memorizing the Qur'an as indicated by the pretest and posttest assessments.